Surface Crystallization of Aqueous Salt Solution Under Overheating and Overcooling - Nakoryakov Vladimir; Misyura Sergei; Morozov Vladimir (MATEC Web of Conferences, 2016)
The investigation of the surface crystallization with low negative and high positive temperatures were carried in the paper. Crystallization curves for distillate (Ts0 = −9 °C) and different mass salt concentrations NaCl (Ts0 = 80 °C) were obtained. Experimental data indicate that the crystallization centers influence each other and the number of centers does not change with time. The maximum speeds for the crystallization front reached 0.3–0.5 m/s. There are a significant anisotropy and a curvature of crystallization front. The surface kinetics should be considered to clarify the rate of freezing and melting of ice in modeling global warming.